2012
DOI: 10.1371/journal.pone.0033212
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Serologic Analysis of Novel and Known Viruses in Species Human Adenovirus D in Which Serology and Genomics Do Not Correlate

Abstract: In November of 2007 a human adenovirus (HAdV) was isolated from a bronchoalveolar lavage (BAL) sample recovered from a biopsy of an AIDS patient who presented with fever, cough, tachycardia, and expiratory wheezes. To better understand the isolated virus, the genome was sequenced and analyzed using bioinformatic and phylogenomic analysis. The results suggest that this novel virus, which is provisionally named HAdV-D59, may have been created from multiple recombination events. Specifically, the penton, hexon, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Recombination of HAdV genomes plays a role in pathogen genesis (3,5,6,8,9,10,12,13). This presentation of the first HAdV-B14 isolate in China facilitates an understanding of the evolution of HAdV-B55 and provides awareness of possible recombination events between wild-type viruses and adenoviral gene delivery vectors, with additional information for the development of adenovirus vaccines.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recombination of HAdV genomes plays a role in pathogen genesis (3,5,6,8,9,10,12,13). This presentation of the first HAdV-B14 isolate in China facilitates an understanding of the evolution of HAdV-B55 and provides awareness of possible recombination events between wild-type viruses and adenoviral gene delivery vectors, with additional information for the development of adenovirus vaccines.…”
mentioning
confidence: 92%
“…To date, 65 HAdV types have been recognized and classified within seven species (5,6,8,(10)(11)(12). Among these, HAdV-B14 has been rarely reported since its identification as an acute respiratory pathogen in The Netherlands in 1955, with a second occurrence in England (1957).…”
mentioning
confidence: 99%
“…Therefore, genetic analysis offers an alternative and accurate method to classify HAdV and provides an opportunity to identify novel HAdV types. Recently, field isolates of novel HAdV types have been documented bearing unique recombination of their genome, and the genetic analysis revealed that majority of these genotypes belong to HAdV-D (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Switching of the hexon variable regions to a low seroprevalence epitope of HAdV-48 (37) and producing the novel combination of the epitope-containing capsid proteins, represented as P65H48F60, may have increased the success rate of host infection by HAdV_Chiba_E086/2012 since the low seroprevalence indicates that only a small number of hosts have experienced HAdV-48-like viruses. The change to the HAdV-GT60-like fiber may have altered the tropism of this virus from bronchoalveolar (as in HAdV-GT59) (6) to ocular (34). If this virus is an adaptive form, it would have the potential to cause epidemic ocular infections.…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few types, such as HAdV-GT54, most of the new genotypes have been suggested to be originated from recombination between the types which were designated by serological typing criteria, i.e., HAdV-1 to 51, particularly in the penton base, hexon and fiber genes (2)(3)(4). It has also been speculated that recombinant viruses exhibiting similar phenotypes to their original viruses (e.g., in tropism and pathogenesis) would have been recognized as known types (3)(4)(5)(6). HAdV-GT53 is one of the most complex recombinant forms at least 4 original viruses were involved in the origin of the HAdV GT53 genome.…”
Section: Introductionmentioning
confidence: 99%